2017
DOI: 10.4049/jimmunol.1700062
|View full text |Cite
|
Sign up to set email alerts
|

Determination of a Key Antigen for Immunological Intervention To Target the Latent Stage of Toxoplasma gondii

Abstract: Toxoplasma gondii , an obligate intracellular protozoan parasite, establishes a chronic infection by forming cysts preferentially in the brain, and up to one third of human population worldwide is estimated to be chronically infected with this parasite. However, there are currently no drugs effective against the cyst form of the parasite. In addition, the protective immunity against the cysts remains largely unknown. We analyzed the molecular mechanisms by which the immune system detects host cells harboring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…The present study was developed in the mountainous region of the state (Venda Nova do Imigrante) for which no previous data on avian toxoplasmosis were available. In Venda Nova do Imigrante, 38% of the evaluated birds exhibited specific antibodies against T. gondii, our results were similar compared to results from backyard chickens in the metropolitan area of Recife (FERNANDES et al, 2016) and in the semiarid region of the state of Pernambuco (SÁ et al, 2017). Venda Nova do Imigrante also has a high prevalence of ocular toxoplasmosis, with 11.27% positive cases (ABREU et al, 1998), and is likely a favourable site for the presence and transmission of the parasite, as the mean prevalence of ocular toxoplasmosis in Brazil is 1.6% (ZANETTI & PLETSCH, 2007).…”
Section: Discussionsupporting
confidence: 84%
“…The present study was developed in the mountainous region of the state (Venda Nova do Imigrante) for which no previous data on avian toxoplasmosis were available. In Venda Nova do Imigrante, 38% of the evaluated birds exhibited specific antibodies against T. gondii, our results were similar compared to results from backyard chickens in the metropolitan area of Recife (FERNANDES et al, 2016) and in the semiarid region of the state of Pernambuco (SÁ et al, 2017). Venda Nova do Imigrante also has a high prevalence of ocular toxoplasmosis, with 11.27% positive cases (ABREU et al, 1998), and is likely a favourable site for the presence and transmission of the parasite, as the mean prevalence of ocular toxoplasmosis in Brazil is 1.6% (ZANETTI & PLETSCH, 2007).…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, CD8 þ cytotoxic T cells first need to recognize T. gondii antigen(s) presented by the major histocompatibility complex class I molecules on the surface of the cyst-harboring cells. Our recent studies identified that the N-terminus region of dense granule protein 6 of the T. gondii, presented by the H-2L d molecule, is a key target for CD8 þ T cells to display their cytotoxic activity 31 ; and that N-terminus region of dense granule protein 6eprimed CD8 þ T cells are able to reduce numbers of cysts in the brain when transferred to infected SCID mice that had already established large numbers of cysts. 31 Therefore, it is most likely that the recognition of the N-terminus region of dense granule protein 6 presented by the H-2L d molecule on the surface of cyst-containing cells by CD8 þ cytotoxic T cells plays a critical role for their attachment to initiate their invasion into the cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies identified that the N-terminus region of dense granule protein 6 of the T. gondii, presented by the H-2L d molecule, is a key target for CD8 þ T cells to display their cytotoxic activity 31 ; and that N-terminus region of dense granule protein 6eprimed CD8 þ T cells are able to reduce numbers of cysts in the brain when transferred to infected SCID mice that had already established large numbers of cysts. 31 Therefore, it is most likely that the recognition of the N-terminus region of dense granule protein 6 presented by the H-2L d molecule on the surface of cyst-containing cells by CD8 þ cytotoxic T cells plays a critical role for their attachment to initiate their invasion into the cysts. Figure 7 Both cysts formed within neurons and astrocytes were destroyed by CD8 þ immune T cells, and the destruction of the cysts was associated with accumulation of Iba1 þ microglia and Ly6C þ inflammatory macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…This is directly related with the complex adaptable nature of this parasite, which is associated with its determinants of high virulence and transmission mode [33]. Insights afforded by ongoing studies and literature reports indicate the significance of the potential negative consequences of latent toxoplasmosis occurring in immunocompetent population, a group which was previously considered to be asymptomatic and uncomplicated [34]. Therefore, latent infection by T. gondii was linked to several diseases and states that impair the complex functioning of the brain [35].…”
Section: Discussionmentioning
confidence: 99%